Elucidating the function of clusterin in the progression of diabetic kidney disease - Mao, Lin; Yin, Ruili; Yang, Longyan; Zhao, Dong (Frontiers in Pharmacology, 2025)
Diabetic kidney disease (DKD) is a common microvascular complication and the main cause of death in diabetic patients. Metabolic disorders can accelerate the occurrence and development of DKD through a variety of ways, Recent studies have found that Clusterin (Clu) levels are associated with renal dysfunction and can be used as a biomarker of renal tubular injury, while preclinical studies reveal its renoprotective function. This article reviews the molecular mechanisms of Clu in the interaction between various cells in DKD. In addition, we discuss the latest research progress of Clu in the field of DKD. This review aims to explore Clu as a potential therapeutic target for DKD and provide some guidance for future clinical treatment.